MADRASAH TEACHERS AS ROLE MODELS OF RELIGIOUS MODERATION - Eny Susiani; Wilis Anggraeni; Nurul Hidayah (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
Religious moderation is currently one of the flagship programs of the Ministry of Religion, therefore it is a necessity that Madrasah teachers should become role models of religious moderation. The author formulates in the formulation of the problem as follows: (1) How is the teacher's understanding of the Internalization of Religious Moderation Values at MAN 3 Banyuwangi, (2) What is the role of the teacher as a Role Model for Religious Moderation Values at MAN 3 Banyuwangi, (3) What are the factors supporting and inhibiting teachers in the Internalization of Religious Moderation Values at MAN 3 banyuwangi. The aims of this study were (1) to find out how much the teacher's understanding of internalizing the values of religious moderation at MAN 3 Banyuwangi, (2) to know the teacher's role as a role model for religious moderation values at MAN 3 Banyuwangi, (3) to know the supporting and inhibiting factors teachers in the Internalization of Religious Moderation Values at MAN 3 Banyuwangi. This research uses a descriptive qualitative approach with a case study type of research. Data collection is done by observation method. Interviews, and documentation. The results of the study show that the teacher's understanding of internalizing the values of religious moderation includes showing exemplary behavior to students, applying tolerance, giving advice, applying discipline. The teacher's method as a role model includes giving understanding, conducting monitoring, seeking students to live up to the values of religious moderation.